The vanishing American lawyer - Morgan, Thomas D. (Oxford University Press, 2010)
"In The Vanishing American Lawyer, Thomas D. Morgan discusses the transformation of the U.S. Legal profession. There remains a need for people who understand law, the institutions that create it, and how to access those institutions' work, but lawyers are no longer uniquely qualified to advise on legal questions. Clients need advisors who are more specialized than many of today's lawyers and who also have expertise in non-legal matters. American lawyers have relied on the idea of professionalism to resist efforts to become better able to meet client needs. Lawyers in other countries, notably Great Britain and Australia, have adapted better. Law schools, too, must recognize the world their students face and prepare them to operate successfully within it." "With a comprehensive understanding of the development of the legal profession, Professor Morgan advises lawyers to prepare for what is ahead. The term "professional" should be applied to praise individuals for skilled and selfless efforts, but professionalism will lead to occupational suicide if it is used as a justification for not seeing and adapting to the world ahead."--Jacket